2018
DOI: 10.1016/s1470-2045(18)30093-7
|View full text |Cite
|
Sign up to set email alerts
|

3 versus 6 months of adjuvant oxaliplatin-fluoropyrimidine combination therapy for colorectal cancer (SCOT): an international, randomised, phase 3, non-inferiority trial

Abstract: SummaryBackground6 months of oxaliplatin-containing chemotherapy is usually given as adjuvant treatment for stage 3 colorectal cancer. We investigated whether 3 months of oxaliplatin-containing chemotherapy would be non-inferior to the usual 6 months of treatment.MethodsThe SCOT study was an international, randomised, phase 3, non-inferiority trial done at 244 centres. Patients aged 18 years or older with high-risk stage II and stage III colorectal cancer underwent central randomisation with minimisation for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
181
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(199 citation statements)
references
References 26 publications
13
181
1
4
Order By: Relevance
“…The risk of long-term neuropathy has been associated with cumulative dose of oxaliplatin in some studies [13,26,27], but not in all [12,28]. In the three registration studies, less neuropathy was noted in the study with 25% lower cumulative dose [4,6].…”
Section: Discussionmentioning
confidence: 97%
“…The risk of long-term neuropathy has been associated with cumulative dose of oxaliplatin in some studies [13,26,27], but not in all [12,28]. In the three registration studies, less neuropathy was noted in the study with 25% lower cumulative dose [4,6].…”
Section: Discussionmentioning
confidence: 97%
“…Our ndings from population-based cancer registry data con rmed that higher chemotherapy RDI was needed in high-risk stage III colon cancers, compared with low-risk cancers, and are consistent with the conclusions from six randomized, phase 3 clinical trials conducted by the International Duration Evaluation of Adjuvant Therapy (IDEA) collaboration, which found that 6 months of FOLFOX particularly bene ted high-risk stage III colon cancers. These clinical trials evaluated whether 3 months of FOLFOX or CAPOX is non-inferior to 6 months of therapy in the rate of disease-free survival at 3 years [4,9,32,33]. Results from a pooled analysis of six trials showed that in stage III colon cancer patients treated with FOLFOX, 6-month therapy had a higher rate of disease-free survival than 3-month therapy, particularly in the high-risk group [9].…”
Section: Discussionmentioning
confidence: 99%
“…In one of the trials comparing 3 vs 6 months of adjuvant FOLFOX or CAPOX, the SCOT trial [11], another patientreported outcome measure than CIPN20, used by Soveri et al [9], the FACT/GOG NTx-4 scale was used. The scores in the 6-month arm (approximately 60% of patients actually received 6 months oxaliplatin) were about twice as high as in the 3-month arm (approximately 85% received 3 months), showing that longer treatment gives more acute and late neurotoxicity.…”
Section: How Much Less Is Seen If 3 Months Of Oxaliplatin Is Given?mentioning
confidence: 99%
“…In the adjuvant setting, two aspects will decrease the use of oxaliplatin. One, and the reason most clinicians likely first think of, is, as described above, the recently reported trials revealing that 3 months of oxaliplatin-containing chemotherapy is for many patients not inferior to 6 months of therapy and that the shorter treatment results in less OIPN [10,11,14]. Since the release of trial data in the spring 2018 and the full publications later in 2018, the duration of adjuvant oxaliplatin-containing treatment has likely been shortened worldwide for many, if not all patients.…”
Section: How Much Less Is Seen If 3 Months Of Oxaliplatin Is Given?mentioning
confidence: 99%
See 1 more Smart Citation